2008
DOI: 10.1097/mlg.0b013e318159aa0d
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Fiber and Versican Distribution Within the Lamina Propria of Fetal Vocal Folds

Abstract: Our findings suggest that collagen and versican distribution and arrangement within the lamina propria in the developing fetus are important for vocalization at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 20 publications
2
18
1
5
Order By: Relevance
“…Histological observations suggest adult lamina propria have a superficial, intermediate, and deep layer, each defined by their relative collagen and elastin content. Analogous studies of fetal lamina propria demonstrates an absence of distinguishable layers, suggesting that maturation of the vocal fold is at least in part dependent on the emergence of a trilayered lamina propria . Another study suggested the evolution from a monolayered lamina propria at birth to a trilayered structure by age 13 years .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Histological observations suggest adult lamina propria have a superficial, intermediate, and deep layer, each defined by their relative collagen and elastin content. Analogous studies of fetal lamina propria demonstrates an absence of distinguishable layers, suggesting that maturation of the vocal fold is at least in part dependent on the emergence of a trilayered lamina propria . Another study suggested the evolution from a monolayered lamina propria at birth to a trilayered structure by age 13 years .…”
Section: Introductionmentioning
confidence: 96%
“…Analogous studies of fetal lamina propria demonstrates an absence of distinguishable layers, suggesting that maturation of the vocal fold is at least in part dependent on the emergence of a trilayered lamina propria. 17 Another study suggested the evolution from a monolayered lamina propria at birth to a trilayered structure by age 13 years. 18 However, a study evaluating the utility of histopathology alone to differentiate layers within the lamina propria found that even senior pathologists were, at best, only capable of distinguishing 1-, 2-, and 3-layered lamina propria 76% of the time.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the trachea, the extracellular matrix of the vocal folds of the larynx (which lie just superior to the trachea) continues to be a popular research topic, including studies of collagen types, elastin, and proteoglycans [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. However, despite the wide variety of trachea characterization efforts, ranging from camel trachea dimensions [37] to dolphin trachea biomechanics [38], and even speculation of airflow in dinosaur tracheas [39], very little is known about the distribution of key extracellular matrix components of the trachea.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, variations were present in the expression of versican. Versican, a large proteoglycan, regulates the water content of tissues, participates in the assembly of different ECM components, and plays an important regulatory role in cell biology [20]. Because of its location, the CPM is subject to more trauma than most limb muscles [6] and is frequently exposed to physical and chemical stressors [5].…”
Section: Discussionmentioning
confidence: 99%